2010
DOI: 10.1007/s12291-010-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effect of carnosine pretreatment on cisplatin-induced renal oxidative stress in rats

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 29 publications
8
59
1
Order By: Relevance
“…Pandir and Kara (2013) clarified that Superoxide Dismutase (SOD), catalase (CAT) and Glutathione Peroxidase (GPx) activities were decreased and malondialdehyde MDA levels were increased in the cisplatin nephrotoxicity group. The obtained results were not in accordance with Noori and Mahboob (2010) who found that oxidative stress is another participating factor associated with cisplatin-induced renal damage. SOD, CAT and GPx activities are increased in cellular membranes due to cisplatininduced nephrotoxicity.…”
Section: Discussioncontrasting
confidence: 94%
“…Pandir and Kara (2013) clarified that Superoxide Dismutase (SOD), catalase (CAT) and Glutathione Peroxidase (GPx) activities were decreased and malondialdehyde MDA levels were increased in the cisplatin nephrotoxicity group. The obtained results were not in accordance with Noori and Mahboob (2010) who found that oxidative stress is another participating factor associated with cisplatin-induced renal damage. SOD, CAT and GPx activities are increased in cellular membranes due to cisplatininduced nephrotoxicity.…”
Section: Discussioncontrasting
confidence: 94%
“…Oxidative stress is another participating factor associated with cisplatin-induced renal damage. SOD, CAT, and GPx activities are increased in cellular membranes due to cisplatin-induced nephrotoxicity (25). Quercetin is a derivative of a natural flavonoid.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, during cisplatin treatment, a robust inflammatory reaction occurs and inflammasomes are also stimulated, further exacerbating renal tissue damage. [18][19][20][21] In our present study, we found that the pretreatment with basal diet supplemented with 2% and 4% O. sanctum significantly attenuated cisplatin-induced nephrotoxicity not only by its antioxidation effect but also by decreasing the expressions of several proinflammatory cytokines. The above findings support the observation of histopathological studies.…”
Section: Discussionmentioning
confidence: 70%